To increase the capability of healthcenter workforce in planning at Deli Serdang District (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Public Health Development Index (PHDI) is an indicator used in cities and districts in Indonesia to assess the achievement of public health development. Deli Serdang District in North Sumatera Province is one of 105 districts in Indonesia which has PHDI below national standard, that is 0,5347 in 2013 and 0,6052 in 2018.Health center is primary health care which is focus on promotive and preventif efforts in their work area. The quality of program planning arrange by health center to do promotive and preventif efforts became one of the factors which influence the achievement of program goal that has impact to the quality of their public health. Hopefully, the planning not only concists of routine program yearly, but inovative. Public services have been carried out to 68 health centre workforce from 34 health center in Deli Serdang District. Workshop has been done in order to increase health center workforce’s capability in planning work program, that is evidence based, based on priority, and integrated. Workshop activities were held for two times, namely 4 and 24 July 2020 in Deli Serdang District Health Office. The activity begun with the provision of material, then the participants worked to arrange their Proposed Activity Plan (RUK) for each of health center.